Pengembangan Hard Skill melalui Media "Kelas Kita" Ditengah Pandemi Covid-19 - Zuftian Aris Achmadi; Faizatul Mufidah; Mahfhudz Idham Kholiq; Mualamatul Musawamah; Muhamad Nailu Syifa’; Noor Azizah (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2021)
The Covid-19 pandemic has caused major changes in almost all aspects of life, one of which is the education system. Changes in the education system make it difficult for students to receive material, especially students at the elementary school and kindergarten levels, because learning that is usually done conventionally has turned into distance learning or is done online, whose implementation cannot be implemented. regardless of the use of information technology. This study aims to "study how to develop skills through one of the learning media "kelas kita" which is a digital-based educational platform. The results and conclusions in this paper show that the media has an important role in the implementation of learning especially during the current Covid-19 pandemic. The media has a role in conducting interactions between educators and students in the implementation of online learning. In addition, the media also plays a role in facilitating educators to deliver learning materials so that learning continues even though it is not done face-to-face. In the implementation of online learning, of course, there are obstacles that become separate challenges for education actors, which are related to academic culture, including values, attitudes, knowledge, skills, as well as the readiness of facilities and infrastructure related to technology. Organizing literacy and training related to the use of technology can be one of the solutions in dealing with some of the challenges of online learning during the current Covid-19 pandemic.